Direct Oxidative Allylic and Vinylic Amination of Alkenes through Selenium Catalysis1. Issue 34 (10th July 2013) - Trenner, Johanna; Depken, Christian; Weber, Thomas; Breder, Alexander
<x xml:space="preserve">Abstract</x> Bringing "N" into the game: The direct chemoselective nitrogenation of unactivated alkenes can be achieved through oxidative selenium catalysis (see scheme). This method provides a broad variety of allylic imides in yields of up to 89 % using N‐fluorobenzenesulfonimide (NFSI) as the terminal oxidant and nitrogen source. Furthermore, an unprecedented selenium‐catalyzed vinylic C(sp2)–H nitrogenation was discovered.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>